Beyond CBD: Inhibitory effects of lesser studied phytocannabinoids on human voltage-gated sodium channels - Milligan, Carol J.; Anderson, Lyndsey L.; McGregor, Iain S.; Arnold, Jonathon C.; Petrou, Steven (Frontiers in Physiology, 2023)
Introduction: Cannabis contains cannabidiol (CBD), the main non-psychoactive phytocannabinoid, but also many other phytocannabinoids that have therapeutic potential in the treatment of epilepsy. Indeed, the phytocannabinoids cannabigerolic acid (CBGA), cannabidivarinic acid (CBDVA), cannabichromenic acid (CBCA) and cannabichromene (CBC) have recently been shown to have anti-convulsant effects in a mouse model of Dravet syndrome (DS), an intractable form of epilepsy. Recent studies demonstrate that CBD inhibits voltage-gated sodium channel function, however, whether these other anti-convulsant phytocannabinoids affect these classic epilepsy drug-targets is unknown. Voltage-gated sodium (NaV) channels play a pivotal role in initiation and propagation of the neuronal action potential and NaV1.1, NaV1.2, NaV1.6 and NaV1.7 are associated with the intractable epilepsies and pain conditions. Methods: In this study, using automated-planar patch-clamp technology, we assessed the profile of the phytocannabinoids CBGA, CBDVA, cannabigerol (CBG), CBCA and CBC against these human voltage-gated sodium channels subtypes expressed in mammalian cells and compared the effects to CBD. Results: CBD and CBGA inhibited peak current amplitude in the low micromolar range in a concentration-dependent manner, while CBG, CBCA and CBC revealed only modest inhibition for this subset of sodium channels. CBDVA inhibited NaV1.6 peak currents in the low micromolar range in a concentration-dependent fashion, while only exhibiting modest inhibitory effects on NaV1.1, NaV1.2, and NaV1.7 channels. CBD and CBGA non-selectively inhibited all channel subtypes examined, whereas CBDVA was selective for NaV1.6. In addition, to better understand the mechanism of this inhibition, we examined the biophysical properties of these channels in the presence of each cannabinoid. CBD reduced NaV1.1 and NaV1.7 channel availability by modulating the voltage-dependence of steady-state fast inactivation (SSFI, V0.5 inact), and for NaV1.7 channel conductance was reduced. CBGA also reduced NaV1.1 and NaV1.7 channel availability by shifting the voltage-dependence of activation (V0.5 act) to a more depolarized potential, and for NaV1.7 SSFI was shifted to a more hyperpolarized potential. CBDVA reduced channel availability by modifying conductance, SSFI and recovery from SSFI for all four channels, except for NaV1.2, where V0.5 inact was unaffected. Discussion: Collectively, these data advance our understanding of the molecular actions of lesser studied phytocannabinoids on voltage-gated sodium channel proteins.